2019
DOI: 10.1007/s00204-019-02632-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel dual reporter embryonic stem cell line for toxicological assessment of teratogen-induced perturbation of anterior–posterior patterning of the heart

Abstract: Reliable in vitro models to assess developmental toxicity of drugs and chemicals would lead to improvement in fetal safety and a reduced cost of drug development. The validated embryonic stem cell test (EST) uses cardiac differentiation of mouse embryonic stem cells (mESCs) to predict in vivo developmental toxicity, but does not take into account the stage-specific patterning of progenitor populations into anterior (ventricular) and posterior (atrial) compartments. In this study, we generated a novel dual repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Furthermore, ORACLE’s modular design is adaptable to any TF or gene of interest. The sum of all these features makes ORACLE a flexible tool well suited both for basic discovery as well as tissue engineering and quality control applications 48,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ORACLE’s modular design is adaptable to any TF or gene of interest. The sum of all these features makes ORACLE a flexible tool well suited both for basic discovery as well as tissue engineering and quality control applications 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted January 31, 2021. ; https://doi.org/10.1101/2021.01.30.428961 doi: bioRxiv preprint interest. The sum of all these features makes ORACLE a flexible tool well suited both for basic discovery as well as tissue engineering and quality control applications 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ATRA promoted the differentiation of H9c2 cardiomyoblast cells, leading to the expression of cardiomyocyte gene expression programs and providing evidence that ATRA is a differentiation inducer of CPCs [68,69]. Additionally, several in vitro studies in PSCs have reported retinoids as specific inducers of the atrial cardiomyocyte cell fate [58,70,71] (Figure 2b). In our own study, dose-and stage-specific effects of retinoids were observed on the differentiation of atrial and ventricular PSC-derived cardiomyocytes using markers of early cardiogenesis to detect differentiation status, mirroring embryonic phenotypes [70].…”
Section: Vitamin a Signaling And Regeneration Of The Myocardiummentioning
confidence: 81%
“…Additionally, several in vitro studies in PSCs have reported retinoids as specific inducers of the atrial cardiomyocyte cell fate [58,70,71] (Figure 2b). In our own study, dose-and stage-specific effects of retinoids were observed on the differentiation of atrial and ventricular PSC-derived cardiomyocytes using markers of early cardiogenesis to detect differentiation status, mirroring embryonic phenotypes [70]. Studies by a separate group showed that the titration of BMP and Activin A were shown to regulate the levels of Cyp26 RA degrading enzymes, thereby potentiating RA response in CPCs and determining whether cells assumed an atrial or ventricular fate [72].…”
Section: Vitamin a Signaling And Regeneration Of The Myocardiummentioning
confidence: 96%
“…Few studies have assessed the potential of a teratogenic drug disrupting epigenetics mechanisms, being these studies restricted especially to alcohol and valproic acid use during pregnancy, and their induced histone hyperacetylation (Tung and Winn, 2010;Gupta et al, 2016;Mazzu-Nascimento et al, 2017). On the other hand, assays in embryonic stem-cells are constantly used in the developmental toxicity field, providing a better comprehension of the drug-induced perturbation in development (Worley et al, 2018;Leigh et al, 2020). These perturbations could be assessed by evaluating how these proteins interact with each other in a biological network, which is systems biology field of research.…”
Section: Introductionmentioning
confidence: 99%